BEAUTY PAGEANT OF COMPANIES: A COMPARATIVE STUDY OF PUBLIC ISSUE OF SHARES FOCUSING SRI LANKAN LAW - Segarajasingham, Shanthi (PEOPLE: International Journal of Social Sciences, 2017)
Public issue of shares, popularly known as IPO (Initial Public Offer), is a method adopted by public quoted companies to raise capital. It is regulated in most of the countries although the standard of regulation differs. Author describes IPO as a beauty pageant since the companies expose themselves by disclosure in order to be selected for the purpose of investment by the public. The regulation of IPO is important due to many reasons, including the involvement of money of the general public and the intangible nature of the financial product that is under issue. The main objective of this study is to analyse the law relating to IPO in Sri Lanka on a comparative analysis in order to identify loop holes. In this regard the comparative jurisdictions selected for this study (United Kingdom and Malaysia) have moved forward by taking away the provisions pertaining to disclosure documents/prospectuses from their companies legislation and have them included under the securities legislation, while Sri Lanka has not done so. The reality, very often, is that the public who subscribe for public issue of shares is not profited because the share prices decline from the purchase price. This is due to shortcomings in the law. The writer finds that the scrutiny mechanism of the regulator/s is unsatisfactory and there is no method adopted to monitor the utilization of funds received by the companies. This research is done mostly using secondary data and a minor part is based on primary data.